2015
DOI: 10.1007/s00401-015-1438-8
|View full text |Cite
|
Sign up to set email alerts
|

IDH mutant diffuse and anaplastic astrocytomas have similar age at presentation and little difference in survival: a grading problem for WHO

Abstract: The WHO 2007 classification of tumors of the CNS distinguishes between diffuse astrocytoma WHO grade II (A IIWHO2007) and anaplastic astrocytoma WHO grade III (AA III WHO2007). Patients with A II WHO2007 are significantly younger and survive significantly longer than those with AA III WHO2007. So far, classification and grading relies on morphological grounds only and does not yet take into account IDH status, a molecular marker of prognostic relevance. We here demonstrate that WHO 2007 grading performs poorly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
194
3
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 291 publications
(231 citation statements)
references
References 25 publications
28
194
3
6
Order By: Relevance
“…Importantly, there were no significant differences in PFS among the three groups when based on grade (II or III). This reinforces prior studies that found no significant prognostic differences between IDH-MT grade II and III tumors [31,32]. In fact, Suzuki et al stated that grade III IDH-MT tumors showed OS comparable to corresponding grade II tumors and recommended managing them as low-grade tumors [33].…”
Section: Discussionsupporting
confidence: 85%
“…Importantly, there were no significant differences in PFS among the three groups when based on grade (II or III). This reinforces prior studies that found no significant prognostic differences between IDH-MT grade II and III tumors [31,32]. In fact, Suzuki et al stated that grade III IDH-MT tumors showed OS comparable to corresponding grade II tumors and recommended managing them as low-grade tumors [33].…”
Section: Discussionsupporting
confidence: 85%
“…Large-scale DNA methylation profiling using Infinium ® HumanMethylation450 beadchip arrays has proven very useful for the elucidation of biologically distinct subgroups of medulloblastoma [10], ependymoma [15], glioblastoma [2,12,19], as well as diffuse and anaplastic gliomas [16,17,23]. In the present study of GC patients, 450k analyses revealed that DNA methylation profiles corresponded to those of several previously defined molecular subgroups of gliomas.…”
Section: Discussionsupporting
confidence: 49%
“…In fact, recent evidence points to only minor differences in clinical characteristics between patients with IDHmut diffuse A II and A III [2,15,18,22]. We strongly recommend to use every possibility to come to this diagnosis by IHC with IDH1-R132H specific antibodies and, if required by sequencing exons 4 of IDH1 and IDH2.…”
Section: Implication For Future Diagnostic Approach To Diffuse and Anmentioning
confidence: 98%